The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1590/1678-7757-2019-0694
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and microbiological evaluation of non-surgical periodontal therapy in obese and non-obese individuals with periodontitis: a 9-month prospective longitudinal study

Abstract: Objective: Obesity is a chronic disease that negatively affects an individual's general and oral health. The present study aimed to compare the clinical and microbiological effects of non-surgical periodontal therapy with the full mouth disinfection (FMD) protocol on obese and non-obese individuals at 9 months post-therapy. Methodology: This clinical study was first submitted and approved by the Ethics Committee. Fifty-five obese patients and 39 nonobese patients with periodontitis were evaluated. The full-mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…More recently, other studies with obese and non-obese individuals demonstrated that obesity status does not impact clinical periodontal outcomes after non-surgical therapy [ 68 , 71 ••, 72 ••, 73 , 84 ••, 85 ]. Those studies demonstrated that periodontal treatment led to a significant improvement in periodontal conditions in both groups in a short term [ 68 , 71 ••, 72 ••, 85 ], 6-month [ 73 ], and 9-month [ 84 ••] follow-up post-therapy (Table 1 ). Conversely, Martinez-Herrera et al [ 70 ••] found a significant difference in the extension of teeth with PD ≥ 4 mm after treatment in 3 months post-therapy when obese was compared to non-obese individuals.…”
Section: Impact Of Obesity On Periodontal Treatmentmentioning
confidence: 99%
“…More recently, other studies with obese and non-obese individuals demonstrated that obesity status does not impact clinical periodontal outcomes after non-surgical therapy [ 68 , 71 ••, 72 ••, 73 , 84 ••, 85 ]. Those studies demonstrated that periodontal treatment led to a significant improvement in periodontal conditions in both groups in a short term [ 68 , 71 ••, 72 ••, 85 ], 6-month [ 73 ], and 9-month [ 84 ••] follow-up post-therapy (Table 1 ). Conversely, Martinez-Herrera et al [ 70 ••] found a significant difference in the extension of teeth with PD ≥ 4 mm after treatment in 3 months post-therapy when obese was compared to non-obese individuals.…”
Section: Impact Of Obesity On Periodontal Treatmentmentioning
confidence: 99%
“…12,[18][19][20][21] Conversely, other studies with obese middle-aged individuals have failed to find differences in the frequency and levels of periodontal pathogens between obese and non-obese individuals. 22,23 In some parts of the Western world, the overall rates of cardiovascular diseases have been decreasing, except among young adult populations which have shown alarmingly high rates. 24 It is unsettling that one of the main reasons for that is the increasing incidence in overweight (OW) and obesity (OB) among them, which is causally related to various aspects of modern lifestyle.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also demonstrated significant correlations between these pathogens and parameters of obesity such as BMI and waist circumference (WC) in adolescents and middle‐aged individuals with chronic periodontitis 12,18–21 . Conversely, other studies with obese middle‐aged individuals have failed to find differences in the frequency and levels of periodontal pathogens between obese and non‐obese individuals 22,23 …”
Section: Introductionmentioning
confidence: 99%
“…Due to its association with impaired immunity and healing (Anderson and Hamm 2014), obesity is thought to adversely affect periodontal treatment success. However, a review of nonsurgical treatment interventions conducted through 2015 (Gerber et al 2016) and more recent studies (Peralta et al 2020; Suvan et al 2020; Zuza et al 2020) show inconclusive results. Several investigators found that improvements in pocket depth or number of teeth with attachment loss were less pronounced after nonsurgical treatment in obese patients compared to nonobese individuals (Offenbacher et al 2009; Suvan et al 2014; Bouaziz et al 2015; Goncalves et al 2015;Suvan et al 2020), while others reported no significant difference in clinical periodontal outcomes (Al-Zahrani and Alghmadi 2012; Altay et al 2013; Peralta et al 2020; Zuza et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, a review of nonsurgical treatment interventions conducted through 2015 (Gerber et al 2016) and more recent studies (Peralta et al 2020; Suvan et al 2020; Zuza et al 2020) show inconclusive results. Several investigators found that improvements in pocket depth or number of teeth with attachment loss were less pronounced after nonsurgical treatment in obese patients compared to nonobese individuals (Offenbacher et al 2009; Suvan et al 2014; Bouaziz et al 2015; Goncalves et al 2015;Suvan et al 2020), while others reported no significant difference in clinical periodontal outcomes (Al-Zahrani and Alghmadi 2012; Altay et al 2013; Peralta et al 2020; Zuza et al 2020). These controlled studies have limitations such as a focus on nonsurgical root planing and scaling or disinfectant only, as well as small sample sizes, and they rarely had follow-up times more than several weeks or months.…”
Section: Introductionmentioning
confidence: 99%